2020
DOI: 10.3390/su12031150
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Financial Education and Consumer Life Satisfaction

Abstract: Sustainable financial education is defined as the continuous input of money and time on financial knowledge education after formal schooling. The purpose of this paper is to examine the impact of sustainable financial education on consumer life satisfaction. Utilizing the dataset of Household Consumer Finance of Chinese Urban Residents in 2012 by the China Financial Research Center of Tsinghua University, the variable of sustainable financial education is constructed through the variables of the necessity of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 50 publications
3
12
0
1
Order By: Relevance
“…In recent decades, the internet's development has fastened liquidity flow 39,40 , creating new complex investment forms 41 . In this way, it has deepened financial education contributions to stock market participation 42 , retirement planning 43 , and investment efficiency 44 . Moreover, Internet development helped the financial field to be more detailed and set the stage for dividing the general economy into specific areas for the urgent need of different industrial economies.…”
Section: Literature Review 21 Financial Education Effectsmentioning
confidence: 99%
“…In recent decades, the internet's development has fastened liquidity flow 39,40 , creating new complex investment forms 41 . In this way, it has deepened financial education contributions to stock market participation 42 , retirement planning 43 , and investment efficiency 44 . Moreover, Internet development helped the financial field to be more detailed and set the stage for dividing the general economy into specific areas for the urgent need of different industrial economies.…”
Section: Literature Review 21 Financial Education Effectsmentioning
confidence: 99%
“…It has also been found that financial education relates positively to consumer satisfaction among individuals with higher education. Therefore, consumers who consider financial education important tend to feel more satisfied (Chen et al ., 2020). It has become obvious that financial education increases financial knowledge (Barua et al ., 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In this study, the data of the variable of consumer confidence in financial goals is not continuous but discrete and ordered. According to Chen et al [44], the approach of Ordinary Least Squares (OLS) regression is inappropriate, which will bring estimation bias. Hence, ordered logistic regression is conducted to investigate the roles of education and financial knowledge in consumer financial confidence.…”
Section: Econometric Specificationmentioning
confidence: 99%
“…Tracing back to the empirical model of prior research in the area of consumer finance [44,45], some demographic and socioeconomic characteristics in determining the degree to which consumers' confidence in reaching a financial goal is regarded as control variables. These variables include marital status (1 stands for married and 0 otherwise), gender (1 represents male and 0 otherwise), race (1 represents non-white and 0 otherwise), age (6 types as 18-24, 25-34, 35-44, 45-54, 55-64, and 65 or older), the number of financially dependent children, work status (Being unemployed or retired, being self-employed, and working parttime or full-time).…”
Section: Variablesmentioning
confidence: 99%